Business owners Approach to Tax Planning in Surat: A Comprehensive Analysis (Journal of Informatics Education and Research, 2024)
Tax planning is a vital component of financial management for entrepreneurs, providing various advantages that promote business expansion, stability, and profitability. Well-implemented tax planning methods enable businesses to reduce their tax obligations by taking advantage of deductions, exemptions, and other legal tax-saving avenues. This approach allows entrepreneurs to enhance cash flow, ensuring a greater amount of capital is accessible for reinvestment and growth, which is essential for the sustained success of any enterprise. This examines the views and significance of tax planning strategies among business owners. The research seeks to assess how entrepreneurs perceive tax planning within their financial frameworks and to investigate the correlation between their demographic characteristics (age, education, and business revenue) and their tax planning strategies. A study of 245 business owners from Surat was conducted, analyzing their dependence on tax consultants, usage of tax-saving tools, and consideration of tax-saving options in their investment choices. The research indicates that business owners heavily depend on tax consultants and integrate tax-saving avenues into their business planning. Furthermore, demographic variables significantly influence business owners' views and satisfaction regarding available tax-saving measures. These insights highlight the necessity for customized tax planning consultancy services tailored to various groups of business owners, leading to more efficient tax management and business advancement.